Posterolateral Elbow Dislocation with Ipsilateral Fractures of Head and Distal End Radius - Vijay C; Mahendra Kumar KL; Manjappa CN; Deepak CD (Online Journal of Health & Allied Sciences, 2011)
Elbow dislocation associated with ipsilateral fracture head and distal end radius is a rare pattern of Injury, although it is common for elbow dislocation and radius fractures to occur separately. We report a case of 35 year-old male who had a posterolateral elbow dislocation with ipsilateral fractures of head and distal end radius that underwent closed reduction and POP application and outcome is excellent with 9 months of follow-up.